2012
DOI: 10.1161/circulationaha.112.134304
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Edema and Endothelial Barrier Dysfunction With Imatinib

Abstract: Background-Tissue edema and endothelial barrier dysfunction as observed in sepsis and acute lung injury carry high morbidity and mortality, but currently lack specific therapy. In a recent case report, we described fast resolution of pulmonary edema on treatment with the tyrosine kinase inhibitor imatinib through an unknown mechanism. Here, we explored the effect of imatinib on endothelial barrier dysfunction and edema formation. Methods and Results-We evaluated the effect of imatinib on endothelial barrier fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
178
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 33 publications
12
178
4
1
Order By: Relevance
“…Previous studies also have revealed barrier-protective effects of imatinib. Imatinib attenuated endothelial barrier disruption induced by thrombin or histamine in vitro and VEGF or murine sepsis (2). Another study demonstrated the capability of imatinib to inhibit endothelial permeability induced by the inflammatory agents VEGF, thrombin, and histamine in human microvascular EC (11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies also have revealed barrier-protective effects of imatinib. Imatinib attenuated endothelial barrier disruption induced by thrombin or histamine in vitro and VEGF or murine sepsis (2). Another study demonstrated the capability of imatinib to inhibit endothelial permeability induced by the inflammatory agents VEGF, thrombin, and histamine in human microvascular EC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the chemotherapeutic drug imatinib, an inhibitor of the Abl family of tyrosine kinases as well as several other enzymes, has both vascular barrier-protective and anti-inflammatory properties (2,61). These intriguing observations suggest that imatinib may be a promising therapeutic strategy for ALI syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations